Analysis of the Media Used by History Teachers in History Learning on Two Schools High School in Semarang City (Case Study at Kolose Loyola Semarang High School and Semarang 5 Public High School) - Winarno, Udin; Purnomo, Arif; Suharso, R (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the consideration of teachers in using instructional media history, the suitability of materials and media used, and the decisive effort needed for instructional media history. This study used qualitative research methods. Data collection techniques are observation, interviews, and documentation—analysis of the data source triangulation. The results of the research showed consideration of teachers in the use of instructional media in Kolose Loyola High School by the lesson plan, the condition of enthusiastic students, and the media; meanwhile, in state senior high school 5 Semarang based lesson plans that have been created with a backup plan if the situation does not support the field. Conformity with the media learning materials used at Kolose Loyola Senior High School, use of textbooks as taught material, and the use of video G30S / PKI material G30S / PKI. In state senior high school 5 Semarang material conformity with the medium used in the material's efforts to maintain the independence of Indonesia, the videos displayed battle to preserve the independence of Indonesia, with the first students tasked to present the various battles that occurred in Indonesia.